An evaluation of involving family caregivers in the self-care of heart failure patients on hospital readmission: Randomised controlled trial (the FAMILY study). (October 2017) - Deek, Hiba; Chang, Sungwon; Newton, Phillip J.; Noureddine, Samar; Inglis, Sally C.; Arab, Ghina Al; Kabbani, Samer; Chalak, Wael; Timani, Nadim; Macdonald, Peter S.; Davidson, Patricia M.
Abstract: Background: The prevalence of heart failure is increasing in Lebanon but to date there is no systematic evaluation of a disease management intervention. Objective: The aim of this study was to evaluate the effect of involving family caregivers in the self-care of patients with heart failure on the risk of hospital readmission. Design: A multi-site, block randomised controlled trial. Settings: The study was conducted over a 13-month period in three tertiary medical centres in Beirut and Mount Lebanon, Lebanon. Participants: Adult patients presenting for an exacerbation of heart failure to one of the study centres were included. Patients with limited life expectancy or physical functionality, planned cardiac bypass or valve replacement surgery, living alone or in nursing homes, or aged less than 18 years were excluded. Methods: Patients allocated to the intervention group and their family caregivers were provided with a comprehensive, culturally appropriate, educational session on self-care maintenance and symptom management along with self-care resources. The usual care group received the self-care resources only. Follow-up phone calls were conducted 30 days following discharge by a research assistant blinded to treatment assignment. The primary outcome was hospital readmission and the secondary outcomes were self-care, quality of life, major vascular events and healthcare utilization. Results: The final sample included 256 patients hospitalized for heart failure randomised into control (130 patients) and intervention (126 patients) groups. The mean age was 67 (SD = 8) years, and the majority (55%) were male. Readmission at 30 days was significantly lower in the intervention group compared to the control group (n = 10, 9% vs. n = 20, 19% respectively, OR = 0.40, 95% CI = 0.02, 0.10, p = 0.02). Self-care scores improved in both groups at 30 days, with a significantly larger improvement in the intervention group than the control group in the maintenance and confidence sub-scales, but not in the self-care management sub-scale. No differences were seen in quality of life scores or emergency department presentations between the groups. More patients in the control group than in the intervention group visited health care facilities (n = 24, 23% vs. n = 12, 11% respectively, OR = 0.39, 95% CI = 0.18, 0.83, p = 0.01). Conclusion: The trial results confirmed the potential of the family-centred self-care educational intervention under evaluation to reduce the risk of readmission in Lebanese patients suffering from exacerbated heart failure. Further research is needed to validate these findings with longer periods of follow-up and to identify the intervention components and intensity required to induce sustained benefits on patients' self-care management and quality of life.